2013
DOI: 10.5897/ajmr2013.6261
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, risk factors and major bacterial causes of bovine mastitis in and around Wolaita Sodo, Southern Ethiopia

Abstract: A cross-sectional study was conducted from November 2011 to March 2012 on lactating dairy cows to determine the overall prevalence of bovine mastitis, identify associated risk factors and isolate the predominant bacterial agents involved in causing mastitis in and around Wolaita Sodo. A total of 349 lactating cows were examined for mastitis using clinical examination and California mastitis test (CMT). Bacteriological methods were also employed to isolate the causative bacteria. An overall 29.5% (95% CI: 24.7,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
10
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 7 publications
9
10
3
Order By: Relevance
“…This study was in contrast to previous reports of Mulugeta and Wassie (2013);Biffa et al (2005) and Tamirat (2007) showed that higher infection in cows is occurred at early stage of lactation followed by late and medium stages of lactation. Radostits et al (2007) suggested that, the mammary gland is more susceptible to new infection during the early and late dry period, which may be due to the absence of udder washing and teat dipping, which in turn may have increased the presence of potential pathogens on the skin of the teat.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This study was in contrast to previous reports of Mulugeta and Wassie (2013);Biffa et al (2005) and Tamirat (2007) showed that higher infection in cows is occurred at early stage of lactation followed by late and medium stages of lactation. Radostits et al (2007) suggested that, the mammary gland is more susceptible to new infection during the early and late dry period, which may be due to the absence of udder washing and teat dipping, which in turn may have increased the presence of potential pathogens on the skin of the teat.…”
Section: Discussioncontrasting
confidence: 99%
“…The current finding of the study is comparably higher than the work of Kerro and Tareke (2003) who recorded 40% in cows and 19% in quarters in Southern Ethiopia. The infection rate in cows was also higher than that of Bitew et al (2010) and Mulugeta and Wassie (2013), who reported an overall prevalence of 28.8% in Bahir Dar and 29.5% around Wolaita Sodo, respectively. Since mastitis is a complex disease and the difference in results could be due to difference in management system of the farm, difference in drug usage and the geographical locations of the studies.…”
Section: Discussionmentioning
confidence: 64%
“…This report is relatively similar with the assertion by [16] that in most countries and irrespective of the cause, the prevalence of mastitis is about 50% in cows and 25% in quarters. Besides, this result was in line with the findings of [22] at Bahir Dar and [23] around Wolaita Sodo, 28.8%, 29.5% in cows respectively. However, the current prevalence is lower when compared with the previous findings as 56% in and around Kombolcha town [24].…”
Section: Discussionsupporting
confidence: 80%
“…Occurrence of mastitis was significantly associated with milking hygienic practice. Cows at farms with poor milking hygiene standard are severely affected (53.69%) than those with good milking hygiene practices (23.20 %) [23,27,34]. This might be due to absence of udder washing, milking of cows with common milkers' and using of common udder cloths, which could be vectors of spread especially for contagious mastitis [16].…”
Section: Discussionmentioning
confidence: 99%
“…Poor udder hygiene (OR = 2.040, 95%CI: 1.184, 3.514) were more likely to be infected with S. aureus. The present observation was in line with the report of Mulugeta and Wassie (2013). Sanitary milking habits are important to avoid the spreading of bacteria or their proliferation.…”
Section: Discussionsupporting
confidence: 80%